MAKNA JIHAD DALAM KERANGKA DAKWAH - Riza Pahlevi (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
Mission at its core meaning is invited to persuasive. Prophet Muhammad as a treatise da'wah carrier has no authority to compel. Reality in the community with a call attempt is often not negligible. When you arrive at the implementation level, should the missionary do with violence in the name of jihad? Or what exactly is the meaning of jihad in the context of propaganda. That is why this paper is derived as a reflection and an attempt to explain how the actual context of jihad and da'wah.